Observation of nm-thin spinterface-like structures in few walled carbon nanotubes by pyrolysis of sulfur/ferrocene mixtures - O Odunmbaku; A Taallah; I Sameera; S Wang; F S Boi (Materials Research Express, 2020)
The observation of rehybridized monolayer interfacial phases between graphene-like systems and monoatomic metal phases (spin-interfaces or spinterfaces) has recently attracted significant attention. Spinterface materials result from chemical interaction between a graphene-based material and the chosen ferromagnetic metal at the atomic level. Despite the significant amount of research, controlled observation of spinterface inside carbon nanotubes (CNTs) has been elusive. Recent works have however reported evidence of monoatomic-iron- diffusion within the graphene walls of CNTs produced by pyrolysis of ferrocene/sulfur mixtures. In this work we demonstrate that formation of these interfacial nm-thin Fe-based superstructures is observable only when certain critical quantities of sulfur are pyrolyzed in a ferrocene vapour (i.e. 2.5 mg to 4 mg). For lower quantities of this precursor (0.4 mg) or with vapour flow rates higher than 11 ml min ^−1 no spinterface-nucleation could be probed. By employing complementary TEM, HRTEM, STEM and XPS methods we suggest that the concentration of sulfur can play a critical role in allowing the uniform nucleation of spinterface structures inside CNTs.